1964
DOI: 10.1525/aa.1964.66.suppl_3.02a00020
|View full text |Cite
|
Sign up to set email alerts
|

“Rhetoric,”“Logic,” and “Poetics” in Burundi: Culture Patterning of Speech Behavior1

Abstract: LEIKEother universal categories of human behavior, speech is the object of diverse, complementary specializations. In the context of the ethnography of speaking, not only the language spoken but also the uses of speech may be assumed to have distinctive culture patterns. Ideally, total anthropological description of the pattern of a culture could well' include its rules and uses of speech, their implementation and violation, and relevant sanctions, positive and negative. Conversely, when inquiry is focused on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…Further, I based my proposal on Hymes' publications in the early 1960s and Kaplan's seminal article in 1966 rather than imagining that Kaplan was drawn to Hymes' ethnography of communication because of his recent interest in ethnography as a framework for writing research. Third, I suggested that Kaplan might have read Albert's (1964) article. I did not propose that Kaplan was influenced by it.…”
Section: The Ethnography Of Speaking/communicationmentioning
confidence: 99%
“…Further, I based my proposal on Hymes' publications in the early 1960s and Kaplan's seminal article in 1966 rather than imagining that Kaplan was drawn to Hymes' ethnography of communication because of his recent interest in ethnography as a framework for writing research. Third, I suggested that Kaplan might have read Albert's (1964) article. I did not propose that Kaplan was influenced by it.…”
Section: The Ethnography Of Speaking/communicationmentioning
confidence: 99%
“…Two years after the publication of Hymes' (1962) article on the ethnography of communication, Albert (1964) published an article entitled '"Rhetoric', 'logic', and 'poetics' in Burundi: cultural patterning of speech behavior". As the title indicates, the paper is an ethnographic study of speech behavior in Burundi, a highly secularized, sophisticated feudal kingdom in Africa.…”
Section: The Ethnography Of Communicationmentioning
confidence: 99%
“…Although Hymes uses the phrase "ethnography of communication" in his introduction to the 1964 special issue of the American Anthropologist, and although the title of the collection is "The Ethnography of Communication", none of the individual authors uses that phrase to refer either to their own work or to the approach in general. Instead, three call the approach the "ethnography of speaking" (Albert 1964:35, Frake 1964:127, Arewa and Dundes 1964; two use "sociolinguistics" as a cover term (Ervin-Tripp 1964:86, 91, Gumperz 1964; and one selection invents an additional term: the "ethnography of speaking folklore" (Arewa and Dundes 1964:72). The remainder of the contributors do not use any term to refer to the approach.…”
Section: Wendy Leeds-hurwitzmentioning
confidence: 99%